Water Quality in Floating Raft Aquaponic Systems With Different Types of Plants in Cultivation of Tilapia (Oreochromis niloticus) - Namia, Novita Redemta D.; Sunadji; Djonu, Asriati (International Journal of Educational and Life Sciences, 2024)
This research aims to determine the effect of the floating raft aquaponic system with different types of plants on water quality in cultivation of tilapia (Oreochromis niloticus) and to obtain plants that are very good for maintaining water stability. This study used a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The parameters tested in this research were phosphate, pH, temperature and DO, with treatments K (control), A (water spinach plants), B (pakchoi plants) and C (lettuce plants). The difference in aquaponic system plants in tilapia (O. niloticus) cultivation had a significant effect on pH and DO. Water spinach plants (Ipomoea reptans poir) were the best plants in maintaining water quality with phosphate values in H56 of 1.41 mg/L, pH 8.51, temperature 25.7°C and DO 8.23 mg/L.